Pertumbuhan dan Hasil Tanaman Kedelai dengan Rhizobacteria Pemacu Pertumbuhan Tanaman dan Pupuk Organik Cair - Adnan, Achmad; Priyadarshini, Rossyda; Purwadi, Purwadi (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Many organic wastes are currently used as organic fertilizers. Giving organic fertilizer to plants has a very good impact on soil and plants. The combination of LOF and PGPR can certainly increase the growth and production of soybean plants. This research was conducted in Tanjung Sari Village, Rembang, Central Java from November 2021 to January 2022. Analytical activities were carried out at the Land Resources Laboratory, Faculty of Agriculture, National Development University